2021
DOI: 10.1093/aje/kwab020
|View full text |Cite
|
Sign up to set email alerts
|

Interpregnancy Interval and Subsequent Severe Maternal Morbidity: A 16-Year Population-Based Study From California

Abstract: Interpregnancy interval (IPI) associates with adverse perinatal outcomes, but its contribution to severe maternal morbidity (SMM) remains unclear. We examined the association between IPI and SMM, using data linked across sequential pregnancies to women in California 1997-2012. Adjusting for confounders measured at the index pregnancy (i.e. the first in a pair of consecutive pregnancies), we estimated adjusted risk ratios (aRRs) of SMM related to the subsequent pregnancy. We further conducted within-mother comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…After subsequently reading the title and abstract, the researchers excluded 1,324 articles. Finally, a total of 41 articles ( 1 3 , 13 – 50 ) were included ( Supplementary Table 2 ) in the meta-analysis after further reading the full text. Supplementary Table 1 showed the characteristics of the excluded studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After subsequently reading the title and abstract, the researchers excluded 1,324 articles. Finally, a total of 41 articles ( 1 3 , 13 – 50 ) were included ( Supplementary Table 2 ) in the meta-analysis after further reading the full text. Supplementary Table 1 showed the characteristics of the excluded studies.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies ( 17 , 37 , 41 , 45 , 50 ) have reported the association between short IPI and comprehensive indicators of maternal morbidity. Stamilio et al ( 17 ) defined the main incidence indicators as any one or more of the following symptoms: uterine rupture, bladder, ureter or intestinal injury, and uterine artery tear.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The short IDI is associated with a number of adverse maternal-fetal outcomes (15)(16)(17)(18). Preterm birth, pregnancy complications, and maternal-fetal mortality are often the primary factors affecting the timing of the next delivery (18,19), while pelvic floor disorders (e.g., postpartum UI) are often overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…Postpartum provision of contraception prevents short interpregnancy intervals, which have been associated with preterm birth and severe maternal and neonatal morbidity. [1] , [2] Half of short interpregnancy interval births in the United States are unintended. [3] , [4] At six weeks postpartum, all contraceptive options are deemed safe, including combined oral, vaginal, and transdermal contraceptives, oral or injectable progesterone, progesterone and copper IUDs, and contraceptive implants.…”
Section: Introductionmentioning
confidence: 99%